La responsabilidad del empleado público en España - León Acosta, Miguel (Revista CES Derecho, 2019)
Las diferentes responsabilidades del empleado público han sido abordadas por la doctrina. Sin embargo, y a pesar de que todas ellas parten de un mismo fundamento: garantizar el correcto funcionamiento de la Administración y del resto de poderes públicos, estas responsabilidades rara vez se estudian de manera conjunta. La presente investigación propone un examen conjunto a las responsabilidades penal y disciplinaria, con especial atención a los principios sustantivos del ius puniendi y a los matices que sufren en atención a la condición de empleado público. El estudio se completa con la revisión de la responsabilidad patrimonial del empleado público, lo que permite contraponer el distinto grado de protección que este recibe en caso de incurrir en responsabilidad punitiva o patrimonial. Liability of public servants in Spain The different types of liabilities of public servants are often the subject of legal studies. Despite the fact that these types of liability are founded by the common need to ensure the proper functioning of public authorities, they are rarely studied together. This research work proposes a joint exam to criminal and disciplinary liabilities of public employees, with particular regard to the substantive principles of the ius puniendi, and the nuances they experience given the special condition of civil servants. The study is completed with an analysis of the civil liability of public employees, allowing us to compare the degree of protection awarded to public servants in both criminal and civil liability scenarios. Keywords: Public Servant, Criminal Liability, Disciplinary Liability, Civil Liability, Proper Functioning of the Public Administration.